Handbook of corrosion engineering - Roberge, Pierre R. (McGraw-Hill, 2000)
Corrosion creates expensive problems in almost every discipline in engineering, in nearly every type of manufacturing, and in construction of all categories. Written by an internationally respected expert and emphasizing computer applications, this just-in-time reference does more than help you understand corrosion. It arms you with ready-to-use procedures for detecting and analyzing corrosion damage -- and preventing corrosion before it takes hold.